Pengaruh Model Pembelajaran Contextual Teaching and Learning ditinjau dari Gaya Belajar terhadap Kemampuan Pemahaman Konsep Matematis - Rani Susanti; Vera Dewi Susanti (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2023)
The capacity of students to learn mathematics and solve mathematical problems depends on their ability to understand mathematical concepts or ideas. This study aims to (1) determine the effect of Contextual Teaching and Learning (CTL) learning model on the ability to understand mathematical concepts, (2) identify the learning style of students in understanding mathematical concepts, and (3) to determine whether there is a relationship between the model and learning style. This type of research is an experiment with a 2×3 research design. Data collection techniques used questionnaires and tests. Two-way ANOVA is the hypothesis test used in the study. Before hypothesis testing, normalization test and homogeneity test were conducted. The results of this study based on the results of the Two Way ANOVA analysis test obtained a significant value of the Learning Model 0.551>0.05 so that H_OA is accepted, a significant value of Learning Style 0.172>0.05 then H_OB is accepted and the Significant Value between Learning Models and Learning Styles obtained is 0.204>0.05 then H_OAB is accepted. This shows that the contextual learning model affects students' ability to understand mathematical concepts. Second, there are differences in how well learners with visual auditory and kinesthetic learning styles understand math concepts and the CTL learning model interacts with learners' learning styles to influence this understanding.